Morfologická a molekulární variabilita, rozšíření a ekologie druhů Lewinskya affinis a Lewinskya fastigiata - Pokorná, Kristýna (Jihočeská univerzita, 2021)
This thesis deals morphological and molecular differentiation of Lewinskya affinis s. str. and L. fastigiata, two closely related and morphologically similar species described already in 19th century but until recently considered synonymous in taxonomic literature. My aims were the thorough morphological description and morphometric analysis of measured characters, evaluation of molecular features and distribution data in selected regions of the Czech Republic.
Morphological and molecular variability, distribution and ekology of Lewinskya affinis and Lewinskya fastigiata species